Pendampingan Sekolah Penggerak Jenjang Sekolah Dasar di Kabupaten Gresik Sebagai Upaya Peningkatan Mutu Kurikulum Operasional Sekolah (KOS) - Achmad Rijanto; Suesthi Rahayuningsih (CV. Multi Kreasi Media, 2023)
The Driving School Program (PSP) launched by the Ministry of Education, Culture, Research and Technology (Kemendikbudristek) was simultaneously implemented in stages starting in the 2022/2023 academic year. Every elementary school (SD) both public and private under the Ministry of Education and Culture simultaneously prepares the School Operational Curriculum (KOS). The partner for this community service activity was UPT SD Negeri 25 Gresik. The problem faced by partners was that there was still a lack of knowledge about the guidelines for preparing KOS using the independent curriculum development guidelines. The purpose of this community service activity was to improve the quality of KOS, in accordance with the existing components of the independent curriculum development. The method used is the mentoring method, both online and offline at partner schools. The result achieved from this service activity was the existence of a KOS document that was in accordance with the independent curriculum development guidelines.